Killing of orangutans in Kalimantan ‐ Community perspectives on incidence and drivers - Emily Massingham; Erik Meijaard; Marc Ancrenaz; Dino Mika; Julie Sherman; Truly Santika; Lengga Pradipta; Hugh P. Possingham; Angela J. Dean (Conservation Science and Practice, 2023)
Abstract Despite decades of conservation management, many orangutan populations are on the brink of extinction. This is primarily due to habitat loss and direct killings. A study from 2008/2009 suggested that killing was impacting orangutan populations at a rate sufficient to cause local extinctions. As an illegal and taboo behavior that is difficult to measure, killing has been severely understudied since. We conducted 431 interviews in 79 villages across Kalimantan in 2020/2021. Ours is the first quantitative field study in more than 10 years to assess the state of killing of orangutans. We aimed to: (1) assess the current state of killing of orangutans in Kalimantan and compare this to the previous study; (2) determine whether conservation projects are affecting killing; and (3) explore drivers of killing. We examined killing of orangutans across villages with forest conservation projects, orangutan conservation projects, and no conservation projects. We assessed the existence of killing and used scenarios to examine perceived norms about illegal behavior relating to orangutans. We then used matching techniques to assess whether projects have any impact on these indicators. Overall, our findings suggest that killing has occurred in recent times, and our data does not indicate a clear attenuation of the behavior. As such, we argue that killing may still present a substantial threat to Bornean orangutan populations. We also found no statistically significant evidence that conservation projects are reducing killing. Conservation project managers could seek to understand the drivers of killing, and to invest in interventions that address these drivers. Research suggests that current allocation of conservation funding has been ineffective at abating orangutan population decline. We argue that a key part of improving Bornean orangutan conservation practice involves directly addressing killing of orangutans and the underlying drivers of killing.